A fault-tolerance control method of load frequency based on reverse behavior reconstruction. Issue 1 (1st February 2022) - Xue, Fei; Zhang, Hanhua; Zhang, Shuang; Zhou, Lei; Yang, Ting; Li, Hao
Abstract: The access of a high proportion of renewable energy and the large-scale application of open sharing communication network are the two main characteristics of modern interconnected power grid. However, the tight coupling between the cyber and physical subsystem makes the malicious network attack and sudden physical failure more likely to cause the collapse of the interconnected power grid. Therefore, a reverse behavior reconstruction strategy is proposed, which does not need to obtain a priori fault information and only depends on the input and output measurements of the system, so as to realize fault tolerance as much as possible. The simulation experiments show that the proposed strategy can achieve the frequency fault tolerance and has better practicability and applicability under complex and diverse fault conditions.